Strategi Pemasaran Produk pada Home and Industry di Koperasi “Fatimah” di Kota Makassar - Amirullah; A. Zulfikar Syaiful; Fitriani; Andi Muara Arumbarkah; Hastuti Mulang; Jayadi; Muhammad Akhsan Tenrisau; Sahari Jafar; Sitti Rahmi Razak; Wahida Amra (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
The women's group at the Fatimah Cooperative will receive training on domestic product marketing as part of this community service project. They are aware that they have been marketing their products online. Apart from offering guidance on marketing tactics that encompass the four Ps: product, price, location, and promotion, the program will also elucidate the effectiveness of these techniques. By comparing their accomplishments with the goals outlined in the strategy, the Fatimah Cooperative will be able to evaluate the effectiveness of their efforts. As a result, for every strategy to be put into practice, a detailed action plan must be prepared. Examples of business marketing strategies that employ SWOT analysis are also included in this exercise. These strategies include analyzing the market, setting goals, integrating marketing tactics, building brand awareness, and focusing on mobile clients.